Oswaldocruzia duboisi (Nematoda, Molineidae): Morphology, Hosts and Distribution in Ukraine - Svitin, R.S.; Kuzmin, Y.I. (Вестник зоологии, 2012)
Oswaldocruzia duboisi Ben Slimane, Durette-Desset et Chabaud, 1993 previously known from France and Bulgaria is reported from Ukraine for the first time. The species was found in the material from 8 amphibian host species, of which Lissotriton montadoni, Triturus cristatus, Mesotriton alpestris, Pelophylax ridibunda, P. lessonae, and Hyla arborea are new host records. Newts (Salamandridae) and green frogs (Pelophylax) are considered to be typical hosts for O. duboisi. Illustrated morphological redescription of O. duboisi based on 141 specimens from various hosts is presented. Вид Oswaldocruzia duboisi Ben Slimane, Durette-Desset et Chabaud, 1993, ранее известный из Франции и Болгарии, впервые обнаружен в Украине. Вид найден в материале от 8 видов амфибий, из которых Lissotriton montadoni, Triturus cristatus, Mesotriton alpestris, Pelophylax ridibunda, P. lessonae и Hyla arborea являются новыми хозяевами O. duboisi. Предполагается, что основными хозяевами O. duboisi являются тритоны (Salamandridae) и зеленые лягушки (род Pelophylax). Представлено иллюстрированное описание O. duboisi по 141 изученному экземпляру от разных видов хозяев.